PWE-364 High fibre diet, low fibre diet or habitual diet for the prevention of radiation-induced toxicity in pelvic cancer: a multi-centre randomised controlled trial. (22nd June 2015) - Wedlake, LJ; Shaw, C; Lalji, A; Mohammed, K; Essapen, S; Whelan, K; Andreyev, J
Abstract : Introduction: An estimated 17, 000 patients a year in the UK receive radiotherapy (RT) for pelvic cancers. Acute damage to normal gastrointestinal mucosa (toxicity) is characterised by an inflammatory response that may respond to altered dietary fibre intake through a range of mechanisms. The aim was to undertake a 3-arm, randomised controlled trail comparing high fibre, low fibre, and habitual fibre diet for the prevention of radiation induced toxicity in the short (6 weeks) and long term (1 year) in patients receiving radical (≥45 Grey) RT for lower gastrointestinal or gynaecological malignancies. Method: Patients were randomised to high fibre (target ≥18 g/d non-starch polysaccharide, NSP), low fibre (≤10 g/d NSP) or habitual fibre (control) groups. The primary end-point was the inter-group difference in change in Inflammatory Bowel Disease Questionnaire – Bowel Subset (IBDQ-B) score: start of RT to nadir (worst) score. Patients completed two 7-day food diaries, daily Bristol Stool Form Scale and a sub-group provided stool samples for faecal short-chain fatty acid (SCFA) analysis. Results: A total of 166 patients were randomised (High: 56, Low: 55, Control: 55); median (range) age: 62.5 (26 – 91) years; males:females 42%:58%; median RT dose: 50.4 Grey; 72% concomitant chemotherapy. NSP intake was significantly different between groups at start and end-RT (p < 0.001 all comparisons). Mean IBDQ-B scores reduced in all groups (worsening symptoms) between start and end-RT, however, the reduction was significantly smaller in the high fibre group (-3.1 ± 13.0) compared with control (-10.8, ± 13.6) (p = 0.007). No significant differences were observed in SCFA concentrations. One year IBDQ-B scores were available for n = 121 (withdrawn: 7; deceased: 9; lost to follow-up: 29) and improved in all groups compared to start-RT. Again the difference between high fibre (+1.6 ± 11.9) and control groups (-6.9, ± 12.5) was significant (p = 0.010). Conclusion: The results show a benefit for increased fibre intake during pelvic RT. However, the findings are equivocal as the fall in IBDQ-B scores at end-RT and at one year were not significantly different between high fibre and low fibre groups. High and low fibre intake may provide benefit via different mechanisms although the possible therapeutic effect of dietary intervention alone cannot be ruled out. A high fibre diet was shown to reduce radiation-induced toxicity in patients undergoing pelvic RT. Disclosure of interest: None Declared.